PENGEMBANGAN SISTEM PENILAIAN PEGAWAI DI PT TELUK LUAS DENGAN METODE AHP DAN BAHASA PEMROGRAMAN PHP DAN DATABASE MYSQL BERBASIS WEB UNTUK PENINGKATAN EFEKTIVITAS PENGAMBILAN KEPUTUSAN - Elvin Tjia; Jhon Very; Hadi Syaputra (Riset Sinergi Indonesia, 2025)
Employee Employee performance evaluation is a crucial aspect of human resource management to enhance decision-making effectiveness in a company. PT Teluk Luas faces challenges in conducting manual performance assessments, leading to subjectivity, delays, and inaccuracies in employee evaluations. Therefore, this study aims to develop a web-based employee evaluation system by implementing the Analytical Hierarchy Process (AHP) method to improve objectivity and efficiency in decision-making. This study employs a software development method using the waterfall model. The system is developed using PHP programming language and MySQL database. Data were collected through interviews and document analysis at PT Teluk Luas to determine the weight of criteria in the AHP method. The system was tested using the black-box method to ensure its functionality. The results indicate that the developed system successfully automates employee evaluation processes, enhances speed and accuracy in criteria calculations, and generates real-time performance reports. The implementation of this web-based system enables more transparent and objective decision-making compared to the previous manual method. Therefore, this system can serve as an effective solution for PT Teluk Luas in improving human resource management quality.